The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/cells8091027
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus (HIV) Infection and Use of Illicit Substances Promote Secretion of Semen Exosomes that Enhance Monocyte Adhesion and Induce Actin Reorganization and Chemotactic Migration

Abstract: Semen exosomes (SE) from HIV-uninfected (HIV−) individuals potently inhibit HIV infection in vitro. However, morphological changes in target cells in response to SE have not been characterized or have the effect of HIV infection or the use of illicit substances, specifically psychostimulants, on the function of SE been elucidated. The objective of this study was to evaluate the effect of HIV infection, psychostimulant use, and both together on SE-mediated regulation of monocyte function. SE were isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 117 publications
(128 reference statements)
3
26
0
1
Order By: Relevance
“…To our knowledge, this is the first study to report on HIV-induced alteration in body fluid EV surface charge. Our observation that HIV infection increased the negative surface charge on BEVs and SEVs ( Figure 3 c) is novel, and in line with the notion that HIV reprograms the epigenome and proteome of host cells [ 86 , 87 , 88 , 89 , 90 , 91 ] and EVs [ 51 , 92 ]. The reason for the differences in surface charge between HIV+ and HIV- BEVs and SEVs is unknown.…”
Section: Discussionsupporting
confidence: 85%
“…To our knowledge, this is the first study to report on HIV-induced alteration in body fluid EV surface charge. Our observation that HIV infection increased the negative surface charge on BEVs and SEVs ( Figure 3 c) is novel, and in line with the notion that HIV reprograms the epigenome and proteome of host cells [ 86 , 87 , 88 , 89 , 90 , 91 ] and EVs [ 51 , 92 ]. The reason for the differences in surface charge between HIV+ and HIV- BEVs and SEVs is unknown.…”
Section: Discussionsupporting
confidence: 85%
“…These results showed that multi-bead gSEC separation could be used to separate a variety of biological samples and that each biofluid (at least those tested here) has a unique characteristic absorbance profile. Since seminal plasma exhibit the most complex absorbance profiles and is of particular interest to our group [ 25 , 26 , 27 , 28 , 29 , 30 ], seminal plasma was used as a prototype biofluid for the characterization of the components in the peaks and the development of the analytical algorithms, as well as the compositional and functional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Transmission electron microscopy analysis of the isolated fractions was conducted as previously described [ 30 ]. Briefly, carbon-coated copper grids were glow-discharged to make the film hydrophilic (Pellco Easiglow, 0.2 mpar, 30 mA, 40 s, negative); then, ten microliters of F1–4 were applied to the grid and allowed to sit for 30 s. After removing the excess samples with filter paper, the grids were washed with distilled deionized water (ddH 2 O) twice, followed by staining with 0.7% uranyl formate solution for 20 s. The grids were allowed to air dry before viewed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because HIV‐induced immune activation is the result of a robust host response characterized by the upregulation of a vast array of genes that control viral replication and antiviral molecules, it is likely that early in HIV infection, SE may inhibit the production of HIV‐induced molecules that exacerbate immune activation while constitutively promoting a compensatory upregulation in expression of genes promoting antiviral immune response or immune suppressor genes. Therefore, SE may serve as a counterbalance to moderate the immunopathological consequences of sustained immune activation, or to mediate alteration in cellular actin cytoskeleton and morphometrics, as is the case for SE from donors that used psychostimulants and are HIV infected or uninfected . This may be particularly important in regulating the susceptibility of immune cells at the site of infection.…”
Section: Discussionmentioning
confidence: 99%